Understanding the Roles of Tris(trimethylsilyl) Phosphite (TMSPi) in LiNi0.8Mn0.1Co0.1O2 (NMC811)/Silicon–Graphite (Si–Gr) Lithium‐Ion Batteries. Issue 15 (8th June 2020) - Liu, Haidong; Naylor, Andrew J.; Menon, Ashok Sreekumar; Brant, William R.; Edström, Kristina; Younesi, Reza
Abstract: The coupling of nickel‐rich LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) cathodes with high‐capacity silicon–graphite (Si–Gr) anodes is one promising route to further increase the energy density of lithium‐ion batteries. Practically, however, the cycle life of such cells is seriously hindered due to continuous electrolyte degradation on the surfaces of both electrodes. In this study, tris(trimethylsilyl) phosphite (TMSPi) is introduced as an electrolyte additive to improve the electrochemical performance of the NMC811/Si–Gr full cells through formation of protective surface layers at the electrode/electrolyte interfaces. This is thought to prevent the surface fluorination of the active materials and enhance interfacial stability. Notably, TMSPi is shown to significantly reduce the overpotential and operando X‐ray diffraction (XRD) confirms that an irreversible "two‐phase" transition reaction caused by the formed adventitious Li2 CO3 layer on the surface of NMC811 can transfer to a solid‐solution reaction mechanism with TMSPi‐added electrolyte. Moreover, influences of TMSPi on the cathode electrolyte interphase (CEI) on the NMC811 and solid electrolyte interphase (SEI) on the Si–Gr are systematically investigated by electron microscopy and synchrotron‐based X‐ray photoelectron spectroscopy which allows for the nondestructive depth‐profiling analysis of chemical compositions and oxidation states close to the electrode surfaces. Abstract : Tris(trimethylsilyl) phosphite (TMSPi) is employed as an electrolyte additive in the LiNi0.8 Mn0.1 Co0.1 O2 /Silicon–graphite lithium‐ion cells. TMSPi functions as a scavenger of both hydrogen fluoride in the electrolyte and adventitious Li‐residue on the Ni‐rich cathode. The nature of cathode electrolyte interphase and solid electrolyte interphase modified by TMSPi is intensively investigated by synchrotron‐based depth‐profiling X‐ray photoelectron spectroscopy.